Assessment Of Health Security In Hospitals: A Systematic Review Of Current Practices And Challenges" In Saudi Arabia: Literature Review 2024 (The Review of Diabetic Studies, 2024)
BackgroundOne of the top priorities of the Saudi government is the development of its Health Security in Hospitals of Challenges" in Saudi Arabia , which has been recognized as one of the most  advanced in the Middle East. In Saudi Arabia, various public and private healthcare facilities, including health security in hospitals and clinics, are supervised by the Ministry of Health (MOH), the primary government body responsible for providing healthcare. In 2024, the Saudi government announced a strategic framework of initiatives to diversify Saudi Arabia’s economy and reduce its dependency on oil. These initiatives cover developing public service sectors, including health, education, infrastructure, recreation, and tourism. As part of the Vision 2030 initiative, the Saudi Health Sector Transformation program was launched in 2024 to enhance healthcare services’ accessibility and quality through a comprehensive, efficient, and integrated health system Health Security in Hospitals has gained significant attention at the national and global levels, “security” is not a simple term; instead, it is “essentially contested” - that is, it induces debates about what it means and how to use it.  Aim of this systematically reviews: To assessment define used in Health Security in Hospitals Current Practices and Challenges" in Saudi Arabia 2024.Method: the research method was a systematic review performed in three stages. The first stage was electronic searching based on selection criteria among multiple sources at various time points during the year 2024. These sources included online literature searches and other governmental health agencies.Results: health security can contribute to the overall patient experience by participating in patient centered initiatives. For example, they can engage in community outreach programs that promote health and wellness, thereby fostering a positive relationship between the healthcare facility and the community it serves.Conclusion:  health security requires more state and international collaboration efforts to reach Global Health Security. To the best of our knowledge, no known government body or organization is responsible for governing health security in Saudi Arabia. However, the current study presents a definition of health security and differentiates it from the public health approach,